Pride’s “This Bed’s Not Big Enough”: Struggle for marital true love - Idha Nurhamidah; Sugeng Purwanto (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
The current study was aimed at investigating the struggle of Charley Pride through his song lyric entitled “This Bed’s Not Big Enough” employing a mixed approach of literary and systemic-functional perspectives to save his marriage in an alternative. The marital problem may go even worst when the memories linger in bed, calling his or her ex’s name on sexual encounters. This really hurts, and may or may not end in a divorce depending on the wife's decision. Upon completion of systemic functional linguistic analysis to construe the meaning of the song, it turns out that the song lyric managed to create a discursive practice that most people would experience when encountered in the same situational context. The solution varies from one individual to another pertinent to one's social and educational background. Therefore, to further confirm the research findings, a supplementary survey to twenty male colleagues (husbands) was conducted to reveal their attitude- moral values and judgments on both implicit and explicit intentions of the song, to extrinsically relate them to a social and religious domain (value). The findings show that alternative solutions differ from one individual to another depending on social, educational and religious backgrounds.